Factors Affecting Borrowers’ Intention in Peer-To-Peer Lending Platform in Mongolia - Gerelt-Od U; Delgertsetseg D; Chimedtsogzol Yo; Oyundari B (Green Publisher Indonesia, 2022)
The current paper aims to examine factors that influence borrowers’ intention to borrow from Peer-to-Peer lending platform in Mongolia. This topic has been attracting researchers’ interest especially since 2008 when the 3rd round of fintech development starts over the developed countries. The most of those studies focus on investigating the factors that explain borrowers’ intention to borrow, and a few of them research this perspective from the investors’ side. It is hardly to find the study that explain intentions of parties to participate in a P2P lending platform in Mongolia. Our research tries to fill this gap by studying factors influencing borrowers’ intention in Mongolian fintech market. We have used the TAM model as a theoretical framework and have collected survey questionnaires from investors and borrowers from all fintech companies in Mongolia. The result shows that borrowers’ intention is mostly driven by initial trust and perceived risk. Other variables, perceived ease of use and perceived security, have no impact on borrowers’ decisions to participate in P2P platform.